Innovative sensing with tapered u-shaped plastic optical fibers: Applications in humidity and formaldehyde detection / Siti Halma Johari - Siti Halma , Johari (2024)

(untitled)
Precise humidity measurements are vital for many applications including food, agriculture, and electronic industries. Continuous exposure to formaldehyde may also cause injury to the central nervous, respiratory, blood and immunological systems. This thesis aims to develop a portable and workable sensing device by generating evanescent waves (EW) on a tapered U-shape plastic optical fiber (POF) coated with Zinc oxide (ZnO) nanorods and Hydroxyethyl cellulose / polyvinylidene fluoride (HEC/PVDF) for relative humidity (%RH) and formaldehyde vapor concentration sensing. The tapered POF was prepared using chemical and mechanical etching techniques. The %RH sensor was successfully developed and optimized using a tapered U-shaped POF coated with ZnO nanorods and HEC/PVDF as a sensing probe. With ZnO nanorods coating, the sensor performance was greatly improved as compared to the uncoated POF. Zinc oxide nanorods were synthesized using the hydrothermal method and grown for 12 hours on the tapered POF. For three source wavelengths of 470 nm, 530 nm and 645 nm, the output voltage of the sensor was found to be inversely proportional to %RH in the range of 35% to 90% RH. The proposed sensor produced the best sensitivity of 0.0231 V/%RH at 645 nm, with a slope linearity of 99.47% and fastest response and recovery times of 61 seconds and 68 seconds respectively. On the other hand, the HEC/PVDF based humidity sensor exhibited the highest sensitivity of 0.0733 V/%RH, with the smallest standard deviation of 0.0034 V when the LED’s wavelength of 645 nm was used. The tapered U-shape POF coated with zinc oxide nanorods was also successfully evaluated at a wavelength of 645 nm for formaldehyde vapor sensing within a concentration range from 5% to 20%. The output voltage of 0.0958 V was observed, with the reduction of formaldehyde concentration from 20% to 0%. This was due to the more scattering effect of ZnO nanorods at 20% of formaldehyde concentration. The sensor response demonstrated an excellent linearity of 98.58% across all vapor concentrations. The sensitivity was measured to be -0.00543 V/%. This study showed that the proposed sensors were simple to fabricate, with the advantages of small size and good repeatability all of which are useful for %RH and formaldehyde sensing applications. The proposed sensor also has the potential to be used to detect air pollution produced, not just by formaldehyde vapor, but also by other dangerous or poisonous vapors or gases.